2007
DOI: 10.1161/circresaha.107.151563
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of Soluble Vascular Endothelial Growth Factor Receptor 1 Contributes to Angiogenesis Defects in the Placenta of α 2B -Adrenoceptor–Deficient Mice

Abstract: Abstract-␣ 2 -adrenoceptors are essential presynaptic regulators of norepinephrine release from sympathetic nerves.Previous studies in mice with targeted deletions in the 3 ␣ 2 -adrenoceptor genes have indicated that these receptors are essential for embryonic development. In the present study, we searched for the ␣ 2 -adrenoceptor subtype(s) involved in placental development and its molecular mechanism using mice carrying targeted deletions in ␣ 2 -adrenoceptor genes. Congenic ␣ 2B -adrenoceptor-deficient mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
26
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 37 publications
0
26
0
2
Order By: Relevance
“…In addition, the ␣ 2B -subtype is unique among the adrenoceptors because it plays an essential role during embryonic development (9,10). Although previous studies have demonstrated the involvement of ␣ 2B -receptors in extraembryonic development (9, 10), i.e.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the ␣ 2B -subtype is unique among the adrenoceptors because it plays an essential role during embryonic development (9,10). Although previous studies have demonstrated the involvement of ␣ 2B -receptors in extraembryonic development (9, 10), i.e.…”
Section: Discussionmentioning
confidence: 99%
“…For this study, Adra2b Ϫ/Ϫ mice, which were backcrossed onto a C57BL/6 background (Harlan Winkelmann, Borchen, Germany) for 12 generations, were used (9). All animal procedures were approved by the responsible animal care committee of the University of Freiburg, Germany.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations